The research of dominant fears in children with cancerous conditions at different stages of treatment - Skakovska , Anastasiia (Psychological Prospects Journal, 2020)
Purpose. The present article provides the research results of fear in primary school-aged children who suffer from hematologic malignancies. It is performed a benchmarking analysis of gender differences of dominant fears in children with hematological malignancies, fulfilled a comparative study of fears in three samples of cancerous patients. The goal of the research is investigation of prevalent fears in children with cancer diagnosis at different stages of treatment. Methods. For performing the tasks of studying children’s fears, the methodology of O.I.Zakharov was applied with the involvement of such processing results methods as comparative analysis (Student's t-test) and one-way analysis of variance (Scheff's criterion). Results. Based on the results of the conducted research it is estimated that cancer-affected girls are characterized by the presence of medical fears, fears of animals, fears of fabulous (fantastic) characters, fear of own death, fear of parents’ death, fear of nightmares, and fears associated with falling asleep. For studied boys with cancer diagnosis it is common to be afraid of physical injures and space fears. It is asserted distinctive dominant fears in cancer pediatric patients with different lengths of hospital stay according to the methodology scale of children’s fears identification. It is established distinctive dominant fears in children with malignancies and relatively healthy children from the control group. It is identified statistically significant discrepancy according to the methodology scale of children’s fears identification between cancer-affected children under study with the experience of transplantation and other patients from the study group as well as difference between the children under study who achieved remission and the ones who have not achieved disease regression yet. Conclusions. According to the conducted research, it is estimated that children with hematological malignancies and relatively healthy children from the control group are characterized by distinctive dominant fears. Ultimately, it is possible to elicit that dominant fears in children with hematological malignancies significantly differ depending on the stage of treatment and these fears are tightly connected with individual (personal) experience of the disease.
Keywords: hematological malignancies; primary school age; psychological peculiarities